1999
DOI: 10.1093/emboj/18.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear targeted delivery of functional NF-kappa B by 70kDa heatshock protein

Abstract: The 70 kDa heat shock protein (Hsp70) is a highly conserved, ubiquitous protein involved in chaperoning proteins to various cellular organelles. Here we show that when added exogenously to cells, Hsp70 is readily imported into both cytoplasmic and nuclear compartments in a cell-type-specific fashion. We exploited this ability of Hsp70 to deliver NF-κB, a key transcriptional regulator of inflammatory responses. We demonstrate that a fusion protein composed of a C-terminal Hsp70 peptide and the p50 subunit of NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 25 publications
(25 reference statements)
5
35
0
Order By: Relevance
“…Whether such receptors exist and bind Hsp70 in neurons has not been investigated. However, in addition to such receptor-mediated activity, there is evidence that HSP70 can be internalized and readily imported into both cytoplasmic and nuclear compartments of arterial smooth muscle cells, U937 cells, lymphocytes, retinal ganglion cells, and neuroblastoma cells (Johnson et al, 1990(Johnson et al, , 1995Guzhova et al, 1998;Fujihara and Nadler, 1999;Guzhova et al, 2001;Yu et al, 2001). Administration of e-rhHsp70 reduces the number of dying motoneurons in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether such receptors exist and bind Hsp70 in neurons has not been investigated. However, in addition to such receptor-mediated activity, there is evidence that HSP70 can be internalized and readily imported into both cytoplasmic and nuclear compartments of arterial smooth muscle cells, U937 cells, lymphocytes, retinal ganglion cells, and neuroblastoma cells (Johnson et al, 1990(Johnson et al, , 1995Guzhova et al, 1998;Fujihara and Nadler, 1999;Guzhova et al, 2001;Yu et al, 2001). Administration of e-rhHsp70 reduces the number of dying motoneurons in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although the best understood role of HSP70 relates to its intracellular functions, secretion or release of HSP70 by one cell population to act on neighboring cells has been suggested (Tytell et al, 1986;Hightower and Guidon, 1989;Guzhova et al, 2001). Although it is unclear how extracellular Hsps function, there is evidence that they can be internalized and readily imported into both cytoplasmic and nuclear compartments of many cell types and that they appear to promote survival (Johnson et al, 1990(Johnson et al, , 1995Houenou et al, 1996;Guzhova et al, 1998;Fujihara and Nadler, 1999;Yu et al, 2001;Tidwell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fujihara and Nadler (1999) showed that exogenous Hsp70s enter certain cells and transport the proteins to nuclei. Schemes to exploit BER enhancement would not be difficult to imagine.…”
Section: Stress-induced Apoptosis Is Influenced By Hsp70mentioning
confidence: 99%
“…Similarly, the same peptide delivered with a different PTD (PTD-5) blocked the adverse effects of the pro-inflammatory cytokine IL-1β on islet cell function [49]. Finally, combinations of hydrophobic and nuclear localization sequence (NLS) peptides have been used to inhibit nuclear translocation of NF-κB [50][51][52].…”
Section: Introduction Of Heterologous Proteins Using Ptdsmentioning
confidence: 99%